Fracture analysis of hydrogen storage composite cylinders with liner crack accounting for autofrettage effect - Hu, J.; Chandrashekhara, K.
An understanding of fracture behavior is crucial to the safe installation and operation of high-pressure composite cylinders for hydrogen storage. This work has developed a comprehensive finite element model to investigate axial surface flaws in cylinder liners using the fracture mechanics and a global-local finite element technique. Since the autofrettage process has a strong influence on cylinder fracture behavior, it is also considered in this analysis. The simulation process is broken down into three steps in order to precisely extract fracture parameters and incorporate the autofrettage effect. In the first step, the global model performs the autofrettage simulation to study the residual stress with consideration of both material hardening and the Bauschinger effect. In the second step, the global model uses residual stress to compute displacement for the local model. Finally, in the third step, the local model extracts the values of stress intensity factor and Jintegral. Comparison is conducted on the fracture parameters with various autofrettage levels and crack shapes. The vicinity of the crack front is also studied by the size and shape of the plastic zone, and the validity of stress intensity factor and J-integral dominances is examined.
Keywords: FRACTURE; HIGH PRESSURE; COMPOSITE CYLINDER; HYDROGEN STORAGE; AUTOFRETTAGE; STRESS INTENSITY FACTOR; J-INTEGRAL